Comparison of real‐world outcomes following immunotherapy in recurrent or metastatic head and neck squamous cell carcinoma with outcomes of randomized controlled trials. Issue 4 (20th February 2023) - Yalamanchali, Anirudh; Yang, Kailin; Roof, Logan; Lopetegui‐Lia, Nerea; Schwartzman, Larisa M.; Campbell, Shauna R.; Woody, Neil M.; Silver, Natalie; Koyfman, Shlomo; Geiger, Jessica L.; Yilmaz, Emrullah
Abstract: Objectives: Evaluate outcomes of patients with recurrent or metastatic (R/M) head and neck squamous cell carcinoma (HNSCC) treated with immunotherapy (IO). Methods: Among patients with R/M HNSCC treated with IO in this retrospective single‐institution cohort, Cox regression was used to compare overall survival (OS) for those with platinum‐refractory disease and those treated in the first‐line setting with OS from KEYNOTE‐040/048, respectively. Multivariable Cox regression was used to identify predictors of OS. Results: There was no significant OS difference for those treated in the platinum‐refractory setting when compared to patients on KEYNOTE‐040 (HR = 1.22, p = 0.27), nor for the first‐line setting compared to KEYNOTE‐048 (HR = 1.23, p = 0.19). ECOG‐PS 1 (HR = 2.00, p = 0.02) and ECOG‐PS 2 (HR = 3.13, p < 0.01) were associated with worse OS. Higher absolute lymphocyte count (ALC) was associated with improved OS (HR = 0.93 per 100 cells/μL, p = 0.03). Conclusions: Real‐world outcomes of IO in R/M HNSCC are similar to outcomes in randomized control trials, with performance status and ALC correlating with OS.